New SAT Math Workbook

To find the value of b substitute either xy value

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: e x + 1 to 3, 8, and 15: (3) + 1 = 4 = +2 (8) + 1 = 9 = +3 (15) + 1 = 16 = +4 ( ) ( ) ( ) ( )( ) 1 4 =2 1 4 1 4 = 1 2 1 2 = 1 4 Another way to solve the problem is to let x = 2 x x , then solve for x by squaring both sides of the equation (look for a root that matches one of the answer choices): x = 2x x 1= 2 x 1 =x 2 1 =x 4 Choice (B) provides the members of the range. Remember that x means the positive square root of x. 2. (E) To determine the function’s range, apply the rule (6a – 4) to –6 and to 4. The range consists of all real numbers between the two results: 6(–6) – 4 = –40 6(4) – 4 = 20 The range of the function can be expressed as the set R = {b | –40 < b < 20}. Of the five answer choices, only (E) does not fall within the range. 3. (D) The function’s range contains only one member: the number 0 (zero). Accordingly, to find the domain of x, let f(x) = 0, and solve for all possible roots of x: x 2 − 2x − 3 = 0 ( x − 3)( x + 1) = 0 x − 3 = 0, x + 1 = 0 x = 3, x = −1 2. (E) First, note that any term raised to a negative power is equal to 1 divided by the term to the absolute value of the power. Hence: a −3 − a −2 = 1 1 − a3 a 2 Using this form of the function, substitute 3 for a , then simplify and combine terms: f 1 ( )= 1 3 () () 1 3 3 1 3 1 − 1 2 = 1 1 27 − 1 1 9 = 27 − 9 = 18 3. (A) In the function, substitute (2 + a) for x. Since each of the answer choices indicates a quadratic expression, apply the distributive property of arithmetic, then combine terms: f (2 + a) = (2 + a)2 + 3(2 + a) − 4 = (2 + a)(2 + a) + 6 + 3a − 4 = 4 + 4 a + a 2 + 6 + 3a − 4 = a 2 + 7a + 6 Given that f(x) = 0, the largest possible domain of x is the set {3, –1}. 4. (B) The question asks you to recognize the set of values outside the domain of x. To do so, first factor the trinomial within the radical into two binomials: f ( x ) = x 2 − 5 x + 6 = ( x − 3)( x − 2) 4. (D) Substitute f(x) for x in the function g(x) = x + 3: g(f(x)) = f(x)...
View Full Document

This note was uploaded on 08/15/2010 for the course MATH a4d4 taught by Professor Colon during the Spring '10 term at Embry-Riddle FL/AZ.

Ask a homework question - tutors are online